Aplikasi Peminjaman Laboratorium Pada Fakultas Teknologi Pertanian Universitas Andalas - Afdal; Novri; Dwiny Meidelfi; Tri Lestari (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2021)
Campus laboratories, especially the Andalas university campus, faculty of agricultural technology, are very important supporting facilities for the continuity of education. In this laboratory, students carry out practical learning which significantly makes students understand the material better. Laboratory management activities at the Andalas campus faculty of agricultural technology are all forms of recording goods and activities that occur in the laboratory. Given the importance of laboratory functions, good laboratory management is an absolute necessity. This allows the campus to more easily get real data from the use of the laboratory by students and activities in the laboratory. This study aims to produce a web and android-based laboratory loan management information system, because compared to a paper basis, laboratory lending and management activities using web and android-based information systems are considered more efficient to implement, because with the web and android all forms of recording can be done easily. easy to do and if data is needed, all authorized parties can easily get the data. The method used in designing this campus laboratory information system uses the waterfall method where this method uses a sequential software lifeflow approach starting from the stages of analysis, design, implementation, testing and maintenance. Based on this research, it is concluded that with the existence of a web and android-based management information system, it is hoped that laboratory loan management activities at the Andalas campus, faculty of agricultural technology will be better.